Clinical effectiveness and safety of aspirin for venous thromboembolism prophylaxis after total hip and knee replacement: a systematic review and meta-analysis of randomized clinical trials - Matharu, G; Kunutsor, SK; Judge, A; Blom, A; Whitehouse, MR (American Medical Association, 2020)
Importance Patients undergoing total hip replacement (THR) and total knee replacement (TKR) receive venous thromboembolism (VTE) pharmacoprophylaxis. It is unclear which anticoagulant is preferable. Observational data suggest aspirin provides effective VTE prophylaxis. Objective To assess the effectiveness and safety of aspirin for VTE prophylaxis after THR and TKR. Data Sources A systematic review and meta-analysis was performed of randomized clinical trials (RCTs), with no language restrictions, from inception to September 19, 2019, using MEDLINE, Embase, Web of Science, Cochrane Library, and bibliographic searches. The computer-based searches combined terms and combinations of keywords related to the population (eg, hip replacement, knee replacement, hip arthroplasty, and knee arthroplasty), drug intervention (eg, aspirin, heparin, clexane, dabigatran, rivaroxaban, and warfarin), and outcome (eg, venous thromboembolism, deep vein thrombosis, pulmonary embolism, and bleeding) in humans. Study Selection This study included RCTs assessing the effectiveness and safety of aspirin for VTE prophylaxis compared with other anticoagulants in adults undergoing THR and TKR. The RCTs with a placebo control group were excluded. The searches and study selection were independently performed. Data Extraction and Synthesis This study followed PRISMA recommendations and used the Cochrane Collaboration’s risk of bias tool. Data were screened and extracted independently by both reviewers. Study-specific relative risks (RRs) were aggregated using random-effects models. Quality of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Main Outcomes and Measures The primary outcome was any postoperative VTE (asymptomatic or symptomatic). Secondary outcomes were adverse events associated with therapy, including bleeding. Results Of 437 identified articles, 13 RCTs were included (6060 participants; 3466 [57.2%] women; mean age, 63.0 years). The RR of VTE after THR and TKR was 1.12 (95% CI, 0.78-1.62) for aspirin compared with other anticoagulants. Comparable findings were observed for deep vein thrombosis (DVT) (RR, 1.04; 95% CI, 0.72-1.51) and pulmonary embolism (PE) (RR, 1.01; 95% CI, 0.68-1.48). The risk of adverse events, including major bleeding, wound hematoma, and wound infection, was not statistically significantly different in patients receiving aspirin vs other anticoagulants. When analyzing THRs and TKRs separately, there was no statistically significant difference in the risk of VTE, DVT, and PE between aspirin and other anticoagulants. Aspirin had a VTE risk not statistically significantly different from low-molecular-weight heparin (RR, 0.76; 95% CI, 0.37-1.56) or rivaroxaban (RR, 1.52; 95% CI, 0.56-4.12). The quality of the evidence ranged from low to high. Conclusions and Relevance In terms of clinical effectiveness and safety profile, aspirin did not differ statistically significantly from other anticoagulants used for VTE prophylaxis after THR and TKR. Future trials should focus on noninferiority analysis of aspirin compared with alternative anticoagulants and cost-effectiveness.